IMPROVEMENT OF QUALITY ASSURANCE SYSTEM ACTIVITIES OF HIGHER EDUCATION INSTITUTIONS - Z. M. Sultalieva (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Abstract. The aim of the article is the improvement of quality assessment system of higher education institutions in the aspect of management. The problems of quality improvement are revealed and classified. The analysis of criteria assessment sets used to define the efficiency of higher education institutions activity is carried out. The components of quality of higher education institutions activity are specified. The structural model of quality assessment system of higher education institutions activity is offered. The analysis of macro environment of a university based on the method of strategic management is carried out, i.e. PEST analysis. As a result of the research a new model of macro criteria model of quality assessment system of higher education institutions, characterizing quality management as an approach to university efficiency is offered, moreover, this system can define the level of its competitiveness in the aspect of quality management.